From Verification-Based Practicum to Product-Oriented Teaching Factory: A Needs Analysis in Chemistry Teacher Education - Ahmadi, Ahmadi; Hakim, Aliefman; Jamaluddin, Jamaluddin; Sumarlan, Iwan; Maripa, Baiq Risni (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Although product-based chemistry practicum and teaching factory studies have been discussed separately, limited empirical diagnostic evidence explains readiness gaps, perception differences, and institutional support needs before a teaching factory-oriented chemistry practicum model is developed. This study aimed to identify empirical needs for developing a product-oriented teaching factory model in chemistry practicum within chemistry teacher education. A descriptive quantitative needs-analysis design was used with substantive interpretation of aggregate questionnaire and observation responses. Participants were 20 chemistry education students and 6 lecturers from two universities in Mataram, Indonesia. The analysis focused on current practicum characteristics, teaching factory understanding and interest, soft skills, barriers, authentic product potential, and partnership needs. The findings indicate that practicum activities remain strongly verification-oriented: 15 of 20 students (75%) reported that procedures strictly followed manuals without modification, while 3 of 6 lecturers (50%) perceived practicum as balanced between verification and exploration. Teaching factory literacy was still limited, with 16 of 20 students (80%) reporting low understanding or no familiarity with the concept. Nevertheless, all students expressed interest in authentic product-based practicum, and all lecturers recognized the importance of developing the model. Main barriers included limited equipment and materials, short practicum time, dense curriculum or standard procedures, and students’ low confidence in trying new approaches. These findings provide initial design considerations, not evidence of model effectiveness. Future development should begin with concept orientation, flexible product-based modules, simple quality testing, structured soft-skill rubrics, and sustainable external partnership mechanisms.